Temple of Aphaia at Aegina
Raking view of standing portions of S colonnade, view NE. In 1658 Ercole Ferrata made a model of a "Cristo Morto" and in 1659 of a "Cristo Vivo" from Bernini's designs. According to Wittkower, these models were cast in bronze twenty-tive times, and twenty-three are still in situ above altars in the basilica. All casts were complete by 1660.